2016
DOI: 10.1016/j.jhsa.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Online Patient Ratings of Hand Surgeons

Abstract: Understanding hand surgeon online ratings and identifying factors associated with positive ratings are important for both patients and surgeons because of the recent growth in physician-rating Web sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 19 publications
(30 reference statements)
4
61
1
Order By: Relevance
“…In our study, we manually searched for self-reported patient data from a popular PRW and observed the majority of patient satisfaction scores for ROs to be in the range of great to excellent. These findings are consistent with our previous work regarding high patient satisfaction with ROs on Healthgrades [ 6 ], patient satisfaction literature examining hand surgeon ratings on three PRWs across the country [ 14 ], and literature on primary care physicians, medical specialists, surgical specialists, and obstetricians and gynecologists who practice in Virginia [ 1 ]. Given the current popularity of PRWs, the findings of this study are directly relevant to patients and ROs and can be viewed as additional data in the growing literature surrounding patient satisfaction.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, we manually searched for self-reported patient data from a popular PRW and observed the majority of patient satisfaction scores for ROs to be in the range of great to excellent. These findings are consistent with our previous work regarding high patient satisfaction with ROs on Healthgrades [ 6 ], patient satisfaction literature examining hand surgeon ratings on three PRWs across the country [ 14 ], and literature on primary care physicians, medical specialists, surgical specialists, and obstetricians and gynecologists who practice in Virginia [ 1 ]. Given the current popularity of PRWs, the findings of this study are directly relevant to patients and ROs and can be viewed as additional data in the growing literature surrounding patient satisfaction.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have looked at the online presence of ROs and determined only 21% of ROs have an online rating on third-party physician rating websites, which is low relative to other specialties [ 23 - 24 ]. This study builds upon previous work by using a much larger sample size of ROs, and our findings indicated that 2679/4444 (60%) of all ROs in the CMS database were found to have a review on Healthgrades.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing websites scores of individual sports medicine doctors revealed a low degree of correlation between websites raising concerns about their reliability [ 19 ]. When reviews were correlated with scores, very high and very low ratings were correlated with the patient’s perception of physician skill and quality, which would seem difficult for patients to truly know [ 20 ]. Similarly, Web-based reviews of hand surgeons showed very positive reviews were related to perceived competence [ 21 ].…”
Section: Discussionmentioning
confidence: 99%